Sinonasal organized Hematoma: Clinical features of seventeen cases and a systematic review. (13th February 2015) - Choi, Soo Jung; Seo, Sung Tae; Rha, Ki‐Sang; Kim, Yong Min
<x xml:space="preserve">Abstract</x> Objectives/Hypothesis Organized hematoma (OH) is a rare non‐neoplastic disease. We studied the clinical characteristics of 17 patients with sinonasal OH and those of 75 cases in the English literature. Study Design Retrospective review of medical records and systematic review of the literature on OH. Methods Comprehensive review of the English‐language literature on OH was performed. We screened all eligible cases based on initial features, and 75 eligible cases found in 15 publications were analyzed. We also retrospectively analyzed and compared medical records of 17 patients diagnosed with pathologically proven sinonasal OH. Data such as demographics, clinical characteristics, pathologic features, radiologic findings, treatment modalities, and follow‐up results were compared to the 75 previously mentioned cases. Results Fifteen cases involved the maxillary sinus, one case involved the frontal sinus, and one case involved the sphenoid sinus. There were six patients over 60 years old, and all were taking an antiplatelet agent. The paranasal sinus computed tomography (CT) of seven patients showed bony destruction of the involved sinus. A review of the available literature revealed mostly similar results with our cases, except for the proportion of patients taking aspirin (5.3%) and sex distribution (male:female = 49:25). Conclusions We reported 17 cases of OH, including a case of frontal sinus and a case of sphenoid sinus lesion. A large proportion of OH patients had bony destruction of the affected sinus on CT. In these patients, a careful diagnosis should be made to distinguish them from a malignant tumor or other expansile diseases. Level of Evidence 4. Laryngoscope, 125:2027–2033, 2015